2014
DOI: 10.1038/cddis.2014.139
|View full text |Cite
|
Sign up to set email alerts
|

Betulinic acid-induced mitochondria-dependent cell death is counterbalanced by an autophagic salvage response

Abstract: Betulinic acid (BetA) is a plant-derived pentacyclic triterpenoid that exerts potent anti-cancer effects in vitro and in vivo. It was shown to induce apoptosis via a direct effect on mitochondria. This is largely independent of proapoptotic BAK and BAX, but can be inhibited by cyclosporin A (CsA), an inhibitor of the permeability transition (PT) pore. Here we show that blocking apoptosis with general caspase inhibitors did not prevent cell death, indicating that alternative, caspase-independent cell death path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
47
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(51 citation statements)
references
References 47 publications
(70 reference statements)
4
47
0
Order By: Relevance
“…MPT is a key event in the mitochondrial apoptotic pathway. BA-induced MPT was a consequence of the opening of the mitochondrial PT pore, which was abolished by cyclosporine A (CsA) or bongkrekic acid [59, 60]. In contrast to these data, we found that cyclosporine failed to alleviate B5G9-induced MPT and cell death (Additional file 2: Figure S1G&H).…”
Section: Discussionmentioning
confidence: 77%
“…MPT is a key event in the mitochondrial apoptotic pathway. BA-induced MPT was a consequence of the opening of the mitochondrial PT pore, which was abolished by cyclosporine A (CsA) or bongkrekic acid [59, 60]. In contrast to these data, we found that cyclosporine failed to alleviate B5G9-induced MPT and cell death (Additional file 2: Figure S1G&H).…”
Section: Discussionmentioning
confidence: 77%
“…MitoTracker ® Orange CMTMRos is a rosamine‐based fluorescent dye that stains mitochondria in live cells. The accumulation of this version of MitoTracker stain is dependent upon membrane potential, such that stain is sequestered into mitochondria in response to highly negative mitochondrial membrane potential (Kholmukhamedov, Schwartz & Lemasters, ; Potze, Mullauer, Colak, Kessler & Medema, ). Potze et al.…”
Section: Methodsmentioning
confidence: 99%
“…Analysis of LC3 puncta was performed using ImageJ software, generating a basal cutoff of LC3 puncta (threshold, 10), then using the Analyze Particle feature for counting to generate a mean of positive pixels per cell (%) AE SEM of three fields of view per sample. 26 Immunofluorescence experiments were performed using this secondary antibody instead of the one previously mentioned, because of the change in confocal microscope.…”
Section: Immunofluorescencementioning
confidence: 99%